Home Procurement Solution: The Utilization of Tawatu’ in the Musharakah Mutanaqishah Agreement for Home Ownership - Jasmin Jasmin; Syaifuddin Syaifuddin; Umu Rosyidah; Muh Sajjaj Sudirman; Abubakar Esa (Business and Applied Management Journal, 2025)
This research aims to examine the application of the tawatu’ concept to enhance the Musharakah Mutanaqishah contract for home ownership financing (KPR), addressing the challenges posed by population growth and housing shortages. Islamic banks offer home ownership financing based on the Musharakah principles, specifically Musharakah Mutanaqishah, which involves a gradual transfer of ownership from the bank to the customer. However, the issue arises from naming the certificate in the customer's name, even though the house remains jointly owned. This study uses field research, collecting data through interviews and document review, and analyzes them using the descriptive qualitative model of Huberman and Miles. The findings indicate that naming the customer on the certificate helps streamline the process with the National Land Agency (BPN), Sharia banks, and the customer. This process is supported by the tawatu’ concept, a secret agreement between two parties aimed at finding a way out of contractual issues within the scope of Sharia law and positive law. The tawatu’ concept provides a harmonious solution for Islamic banking, supporting further growth and development.